Effect of hydrophilic graphite flake on thermal conductivity and fracture toughness of basalt fibers/epoxy composites. (15th November 2018) - Kim, Seong Hwang; Heo, Young-Jung; Park, Mira; Min, Byung-Gak; Rhee, Kyong Yop; Park, Soo-Jin
Abstract: In this work, we fabricated basalt fiber-reinforced epoxy composites using natural graphite flakes. The composites were reinforced with various concentrations of natural graphite flakes. Natural graphite flakes significantly enhanced the mechanical properties of the composites, such as the critical stress intensity factor (KIC ) and critical strain energy release rate (GIC ). In particular, basalt fiber-reinforced composites containing 20 wt% of natural graphite flakes exhibited highest mechanical behavior compared. The fracture toughness mechanisms were illustrated using a crack theory based on morphology analyses of fracture surfaces. In addition, the composites exhibited high thermal stability and thermal conductivity, attributed to the exceptional thermal stability and thermal conductivity inherent in the natural graphite flakes. We observed a direct linear relationship between thermal conductivity and fracture toughness through certain polar components of surface energy. The natural graphite flake particles improved mechanical and thermal properties by performing a crack pinning role in the epoxy-matrix composites.